2007
DOI: 10.1073/pnas.0700617104
|View full text |Cite|
|
Sign up to set email alerts
|

Saposin B is the dominant saposin that facilitates lipid binding to human CD1d molecules

Abstract: CD1d molecules bind lipid antigens in the endocytic pathway, and access to the pathway is important for the development of CD1d-restricted natural killer T (NKT) cells. Saposins, derived from a common precursor, prosaposin, are small, heat-stable lysosomal glycoproteins required for lysosomal degradation of sphingolipids. Expression of prosaposin is required for efficient lipid binding and recognition of human CD1d molecules by NKT cells. Despite high sequence homology among the four saposins, they have differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
93
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 45 publications
2
93
0
2
Order By: Relevance
“…Indeed, using a combination of reagents that selectively recognize CD1d bound to ThrCer or GalGalCer, we have been able to demonstrate specific lipid exchange occurring in the SPR assay. In agreement with results shown by Zhou et al (9) and Yuan et al (8), saposin B alone (not precomplexed with an iNKT cell agonist) could not remove lipids already bound to CD1d molecules, unlike what has been shown for CD1e (57). However, we have shown that lipid-loaded saposin B specifically increased the offrate of lipids bound to CD1d molecules.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Indeed, using a combination of reagents that selectively recognize CD1d bound to ThrCer or GalGalCer, we have been able to demonstrate specific lipid exchange occurring in the SPR assay. In agreement with results shown by Zhou et al (9) and Yuan et al (8), saposin B alone (not precomplexed with an iNKT cell agonist) could not remove lipids already bound to CD1d molecules, unlike what has been shown for CD1e (57). However, we have shown that lipid-loaded saposin B specifically increased the offrate of lipids bound to CD1d molecules.…”
Section: Discussionsupporting
confidence: 81%
“…Together, these results highlight the important role of saposins as lipid-editors for CD1d antigen presentation, in addition to GM2a (9) and Niemann Pick type C2 protein (NPC2) (58). In contrast to DM molecules, which edit the repertoire of peptides bound to MHC class II molecules (59), saposins do not have an enzymatic mechanism of action and we and others have not been able to demonstrate physical association with human CD1d molecules (8), unlike what has been shown for murine CD1d and saposin A (9) or human CD1b and CD1c and saposin C (7,11). Despite extensive in vivo and in vitro studies, the ultimate mechanism of hydrolase activation by saposins is unclear and that of lipid transfer onto CD1d molecules remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations